Mutations in Human Immunodeficiency Virus Type 1 RNase H Primer Grip Enhance 3′-Azido-3′-Deoxythymidine Resistance - Delviks-Frankenberry, Krista A. (American Society for Microbiology, 2007)
We recently observed that mutations in the human immunodeficiency type 1 (HIV-1) reverse transcriptase (RT) connection domain significantly increase 3′-azido-3′-deoxythymidine (AZT) resistance up to 536 times over wild-type (WT) RT in the presence of thymidine analog resistance mutations (TAMs). These mutations also decreased RT template switching, suggesting that they altered the balance between nucleotide excision and template RNA degradation, which in turn increased AZT resistance. Several residues in the HIV-1 connection domain contact the primer strand and form an RNase H primer grip structure that helps to position the primer-template at the RNase H and polymerase active sites. To test the hypothesis that connection domain mutations enhanced AZT resistance by influencing the RNase H primer grip, we determined the effects of alanine substitutions in RNase H primer grip residues on nucleoside RT inhibitor resistance in the context of a WT, TAM-containing, or K65R-containing polymerase domain. Ten of the 11 RNase H primer grip mutations increased AZT resistance 20 to 243 times above WT levels in the context of a TAM-containing polymerase domain. Furthermore, all mutations in the RNase H primer grip decreased template switching, suggesting that they reduced RNase H activity. These results demonstrate that mutations in the RNase H primer grip region can significantly enhance AZT resistance and support the hypothesis that mutations in the connection and RNase H domains can increase resistance by altering the RNase H primer grip region, changing interactions between RT and the template-primer complex and/or shifting the balance between the polymerase and RNase H activities.